GNSS Signal Monitoring and Security of Supply of GNSS-Based Services - Saajasto, Mika; Kaasalainen, Sanna; Mäkelä, Maija; Bhuiyan, M. Zahidul H.; Koivula, Hannu; Kirkko-Jaakkola, Martti; Kuusniemi, Heidi (Springer, 2024)
The global GNSS markets are expected to grow considerably in future, thus the number of threats against GNSS services will also increase. Understanding how GNSS services are utilized on a national level is crucial for the resilience, safety and quality of these services. This study summarises interviews of authorities and specialists in the given GNSS segments, national and international research on related GNSS markets and analysis of related technologies. We provide an introduction to the current state of GNSS-based services, important shortcomings related to security of supply, and the GNSS user needs in relation to GNSS security of supply. We discuss ways to mitigate threats aimed against GNSS services, for example GNSS monitoring and provide suggestions to improve the security of supply of GNSS services. The GNSS markets are becoming increasingly vulnerable to interference, thus resilient navigation and timing solutions are needed. The authentication services of the Galileo-system are aimed to solve these problems, but they are not fully operational. The security of supply and the safety of the GNSS-based services should become a key feature in national cyber-security planning.
Keywords: Critical Infrastructure; GNSS; Security of Supply; fi=Tietotekniikka|en=Computer Science|